Estudio de factibilidad para la creación de una empresa comercializadora de caña bambú para el sector de la construcción en Manabí. - Hidrovo De La Torre, Erika Cecilia (2018)
Given the convergence of social, economic and environmental changes at present, the planning of projects that measure the feasibility of investment in technical, economic-financial, market and environmental aspects becomes relevant. The objective of the study was to analyze the aforementioned aspects, initially applying a survey to a sample of the economically active population of Manabí, determined by means of the finite population formula, the data collected allowed analyzing the market and diagnosing aspects related to preferences, perspectives of the population, market situation and the level of acceptance of the project; in addition, an internal and external analysis of the company was carried out to implement a marketing plan for bamboo. Added to this, in the technical study, the physical-real capacity of the company and its operational structure were identified; while the financial evaluation indicated the required investment resources and profitability indicators. From the study applied, an investment of $57,679.80, required to initiate the start-up of the project, is determined; while the profitability indicators show a NPV of $27,282.99, IRR of 47.76%, with a cost-benefit ratio equivalent to $ 1.19, reflecting this return on investment.